Software development superstream : becoming a senior software engineer. (O'Reilly Media, Inc., 2022)
As software development grows more complicated and becomes increasingly central to a business's identity, the demand is high for developers who operate at a senior level. Join us to level up your skills and accelerate your journey to senior software engineer. These in-depth sessions cover some of the biggest challenges facing software developers today, teaching you practical methods and best practices to improve coding and software design, better manage data, mentor new engineers, and collaborate with your team. About the Software Development Superstream Series: This recording of a live event will help you elevate your technical skills, become a better project manager, and build the other professional skills that will allow you to move into senior engineering roles. What you'll learn and how you can apply it Learn how to contribute at a high level, drive big projects, and determine tech strategy Understand how to change your mindset from doing it yourself to leading your team Discover how your skills stack up against senior and staff roles This recording of a live event is for you because... You're a developer who wants to learn the skills you need to move to the senior or staff level. You want to better understand what work matters the most at every stage of your career and learn how to build the skills you need to get there. You want to find your skills gaps and upskill accordingly. Recommended follow-up: Read The Staff Engineer's Path (early release book) Read Software Engineering at Google (book) Listen to The Manager's Path (audiobook) Read Mentoring (book) Take From Developer to Software Architect (live online training course with Nathaniel Schutta) Take Fundamentals of Software Engineering in 3 Weeks (live online training course with Nathaniel Schutta) Take Hands-On Software Design (live online training course with Venkat Subramaniam) Take Introduction to Critical Thinking (live online training course with Connie Missimer).